Assessment of Metal(loid)s and Nonmetals Contamination in Soils of Urban Ecological Parks in Brazil: Implications for Ecological Risk and Human Health - Fernanda Guerreiro de Paula; Igor Domingos de Souza; Elaine Silva de Pádua Melo; Marta Aratuza Pereira Ancel; Diego Azevedo Zoccal Garcia; Danielle Bogo; Rita de Cássia Avellaneda Guimarães; Karine de Cássia Freitas Gielow; Rodrigo Juliano Oliveira; Gisele Melo Sanches; Priscila Aiko Hiane; Valter Aragão do Nascimento (Urban Science)
Metal(loid)s and nonmetals in the soil of urban parks can pose risks to human health. Thus, we aimed to study the soil elemental content, soil types and their pH, contamination factor, geo-accumulation index, pollution load index, total carcinogenic risk, and hazard quotient for children and adults by ingestion, inhalation, and dermal routes contact in ecological parks (EP) in Central-West Brazil. In Lago do Amor EP, high concentrations of Mg and Mn and lower pH values predominate, while in the Águas do Prosa EP, there is a greater influence of Zn. Except for the range of average concentrations of Al, Fe, P, Mg, and Mn in all EP soils, the range of the average concentrations of As, Cd, Co, Pb, Cr, Cu, Mo, Se, and Zn were generally higher than those permissible limits. There is moderate contamination by Mo, Ni, Cd, and mainly Se in Lago do Amor, Anhanduí, and Sóter EPs. The geo-accumulation index revealed that Lago do Amor EP is moderately polluted by Cd. Oral ingestion was evidenced as the main route of possible contamination by heavy metals, especially for children, who presented a carcinogenic risk greater than 10−1 for As, Cr, and Ni.